THE EFFECT OF ENVIRONMENT AND SELF-REGULATED LEARNING ON LEARNING ACHIEVEMENT OF GRADE XI STUDENTS IN ECONOMICS SUBJECTS AT EAST JAKARTA SENIOR HIGH SCHOOL - Himmatus Sa’idah; Siti Nurjanah; Sri Indah Nikensari (International Journal of Economy, Education and Entrepreneurship, 2022)
This study aims to determine the extent to which environment and students' abilities to self-regulate their learning impact the academic achievement attained by students in the eleventh grade of the East Jakarta Senior High School's economics programme. The methodology of this study is based on quantitative research and includes survey methods. The sampling technique uses simple random sampling, a random sampling technique by selecting one class XI MIPA and one class XI IPS at each school as a representative sample with a sample of 88 students from 736 students. The data collection technique is in the form of a questionnaire in the form of a closed list of statements via a google form link, documentation, namely data in the form of the number of students and data from the Middle Semester Assessment (PTS) and economics teacher interviews. Data analysis used path analysis with IBM Statistics 25. The results of this study indicate that there is a positive and significant influence between the learning environment on learning achievement as evidenced by the t-count ≥ t-table (3.452 > 1.983), there is a positive effect and powerful between self-regulated learning on learning achievement as evidenced by the value of t-count ≥ t-table (9.616 > 1.983) and there is a positive and significant effect between learning environment on self-regulated learning as evidenced by the weight of t-count ≥ t-table (2.092 > 1,983). Following the analysis presented above, one can reach the following conclusion regarding the relationship between the environment and the ability to self-regulate one's learning: there is a positive and significant influence